32.2k views
1 vote
Given f(x) = 4x + 1 and g(x) = A, choose
the expression for (fºg)(x).

Given f(x) = 4x + 1 and g(x) = A, choose the expression for (fºg)(x).-example-1

2 Answers

3 votes

Answer:

4x^4 + 1.

Explanation:

(fºg)(x) = 4(x^4) + 1

- you replace the x in f(x) by A.

User EngineerX
by
6.0k points
3 votes

Answer:

4x^4 + 1

Explanation:

it is same with the question you posted previously

take whole g(x) equation and replace it with the x in the f(x) function

(fog)= 4 ×(x^4) + 1 ➡ 4x^4 +1

User Raberana
by
6.2k points